Pemanfaatan Buku Resep sebagai Strategi Pemberdayaan Peserta Posyandu Melati untuk Cegah Stunting - Talitha, Azzahra Nasywa; Novitasari, Ananda Putri; Nabilla, Rhainaya; Haryanti, Ananda Putri; Riyan, Muhammad Khoirur; Nugraha, Joko Tri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The abstract should end with a comment about the importance of the result or a brief conclusion. This study raised the problem of the high stunting rate in Ngropoh Village which was influenced by the low knowledge of Posyandu participants mothers about balanced nutrition and proper parenting. The method used is Participatory Action Research to increase public involvement in socialization activities and to provide local ingredient-based nutritional food recipe manuals as a preventive measure for stunting. Activities include counseling, distribution of recipe books, and provision of nutritious supplementary food for toddlers. The outcomes of the activity indicated a notable rise in the participants' understanding of how crucial balanced nutrition and a supportive diet are for children's development. The active participation of mothers and Posyandu cadres managed to encourage changes in parenting behavior and better food consumption among participating families. The study's conclusion confirmed that education based on the provision of nutritional and easy-to-access breastfeeding food is very effective as a sustainable strategy to reduce stunting risk.